2003
DOI: 10.1111/j.1549-0831.2003.tb00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Inequity: An Analysis of Large‐Scale Hog Operations in 17 States, 1982–1997*

Abstract: This study extends ideas of environmental equity to large‐scale hog operations. We investigate counties in 17 hog producing states to determine whether large‐scale hog operations are more likely to be sited and expanded in areas that have a disproportionate number of Black, Hispanic, and/or economically disadvantaged residents. The data for this work come from the U.S. Department of Agriculture and the U.S. Bureau of Census. We discover evidence of racial inequity, but only in those states where large‐scale op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Though an important finding, it does not explain the complexity of variations in ecological degradation, or socioeconomic inequality, within industrialized nations. For example, several studies in the US have found that large corporations take advantage of uneven policies and economic inequality when citing their CAFOs, leading to a ''geographic concentration of hog production'' (Welsh et al, 2003: 227; see also Stretsky et al, 2003). Therefore, uneven geographic development does not only occur in developing or transitional countries.…”
Section: Geographic Variation In the Context Of Neo-liberal And Ecolomentioning
confidence: 93%
See 3 more Smart Citations
“…Though an important finding, it does not explain the complexity of variations in ecological degradation, or socioeconomic inequality, within industrialized nations. For example, several studies in the US have found that large corporations take advantage of uneven policies and economic inequality when citing their CAFOs, leading to a ''geographic concentration of hog production'' (Welsh et al, 2003: 227; see also Stretsky et al, 2003). Therefore, uneven geographic development does not only occur in developing or transitional countries.…”
Section: Geographic Variation In the Context Of Neo-liberal And Ecolomentioning
confidence: 93%
“…Welsh et al (2003: 227) find that, in the US, large corporations take advantage of uneven policies and economic inequality when citing their CAFOs, leading to a ''geographic concentration of hog production.' ' Stretsky et al (2003) found in a study of seventeen US states that CAFOs tend to be concentrated in areas with high percentages of minorities. This suggests that vulnerable populations are less able to resist these LULUs.…”
Section: Geographic Variation In the Context Of Neo-liberal And Ecolomentioning
confidence: 94%
See 2 more Smart Citations
“…Eventually, the government paid to relocate love Canal residents, and much of the site remains closed today, more than 35 years after its discovery. This short story plays out across america in numerous large and small cities, affecting the ecological disorganization of urban areas-not to mention 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 A Green Criminological Approach to Social Disorganization 171 rural areas as well-areas for future green criminological investigation, though some literature on mountaintop removal in green criminology and hog farming has already addressed these forms of rural ecological disorganizations (for example, see, Stretesky, Johnston, and arney, 2003). our point is that economic organization and the capitalist treadmill of production lies behind environmental problems, whether those problems are social disorganization or urban ecological disorganization, or even more far-reaching consequences and related environmental issues.…”
Section: Urban Ecological Disorganization and Capitalismmentioning
confidence: 99%